A Missing Link in the Islamic Renaissance - Ahmad Amin (International Institute of Islamic Thought, 1991)
There is a missing link in Egypt. Although it is one of the strongest pillars upon which we are building our renaissance, we hardly ever perceive its presence in our academic circles. This absence is one of the reasons for the poverty of our scientific and intellectual production. And what is this missing link? To be precise, it is scholars who combine in their persons elements of both Arab-Islamic culture and the precise scientific European culture. We are in need of more people like them, for we cannot regenerate ourselves without them, and we can only follow this path by making use of their light. Most of our scholars have only been educated in Arab-Islamic culture. As a result, they are totally ignorant of what is happening in the modem world in relation to the opinions and views being expressed in science, literature, and philosophy. They have not heard of Kant and Bergson, or of Europe’s authors and poets, scientists and researchers. At best, these names are mentioned in insignificant magazines, newspapers, and books devoid of any scientifichtellectual value. The other group of our scholars is made up of those who have been educated solely in a foreign culture. They know all about the latest theories in the fields of physics, chemistry, and mathematics which have reached them, and they follow the developments in modem European literature as well as the books and poetry written by Europeans. They are also familiar with the development of philosophical views and their progress up to our time, but, they are totally ignorant of Arab-Islamic culture. If you tell them of Jarir, al Farazdaq, and al Akhtal, they turn their faces away and avoid you-as if you were talking about a world not our own. If you mention al Kindi, al Farabi, and Ibn Sina, they say that they have heard the names but have no more knowledge of them, and that all we receive from them are ambiguous sentences and profound concepts which neither have scientific or intellectual benefit nor enrich or revitalize life. Yesterday I was talking with a group of these educated people about al Biruni, the Muslim mathematician who died in 440 AH, and the mathematical and astronomical theories he had discovered. I also mentioned that the German orientalist Sachau had decided that al Biruni was the most brilliant man the world has ever known, and that this orientalist had called for the establishment of the al Biruni Society to honor him and to revitalize his memory. The people ...